Induced tooth movement: standardization of terms to describe the effects of forces on the periodontal ligament: compression/Traction instead of Pressure/Tension - Alberto Consolaro (Dental Press Editora, 2012)
There is no reason for Dentistry to use different terms for phenomena defined in Physics, the specific field in which concepts associated with forces are established and adapted. In place of pressure/tension, the compression/traction pair should be used. This study defines each one of these terms and justifies their use. Our contemporary world demands standardized criteria, methods, measures, concepts and terms to ensure that study protocols, results and applications are used in the same way in any country or area of human action.